Student Cadets' Experiences with Social Barriers in Adjusting to Dormitory Life - Sierra Sinta Sunarso Putri; Zunaina Zamhariri; Aqila Nadra Rabbani (International Conference on Psychology and Education (ICPE), 2025)
This paper discusses a case of socialization difficulties experienced by subject N.D.A, a second-year student at Politeknik Pelayaran Surabaya. Primary complaints include significant anxiety related to her sea practical training (Prala) placement, hindrance in completing her final assignment due to difficulty finding references, and struggles with peer socialization. The subject exhibits an introverted personality, high social anxiety, and trust issues stemming from past traumatic experiences. Proposed interventions include supportive counseling, positive affirmation techniques, and emotional regulation development through diary writing, aiming to reduce emotional isolation, manage anxiety, and build self-confidence in interactions.